Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga Terhadap Keputusan Pembelian Pada Coffee Shop - Soesanto, Aldian Ramadhan; Arsyad, Annisa Wahyuni (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
The current business competition is very intense, where every company is required to meet consumer needs while striving to create products that have advantages and are different from competitors. This study aims to examine the effect of product quality, service quality, and price on the purchasing decisions at Coffee Shop Janji Jiwa in Samarinda City. The research method uses a quantitative approach with a survey technique, utilizing a questionnaire distributed to 100 respondents. The sampling technique used is Purposive Sampling, and the data analysis method applied is multiple linear regression analysis. The partial test results show that product quality has a positive and significant effect on purchasing decisions, with a t-statistic value greater than the t-table value of 3.334 > 1.660 and a t-significance value smaller than 0.050 < 0.001. Service quality does not have a positive and significant effect on purchasing decisions, with a t-statistic value smaller than the t-table value of 0.709 < 1.660 and a t-significance value greater than 0.050 > 0.480. Price has a positive and significant effect on purchasing decisions, with a t-statistic value greater than the t-table value of 4.521 > 1.660 and a t-significance value smaller than 0.050 < 0.000. The simultaneous test results indicate that product quality, service quality, and price collectively have a significant impact on purchasing decisions, with an F-statistic value of 42.720 and a significance value of 0.000, which is greater than α = 0.05